Characteristics of Child Fatalities that Occur in the Context of Current or Past Intimate Partner Violence: a Scoping Review - Graham, Laurie M.; Jun, Hyun-Jin; Kim, Jeongsuk; Power, Luke; Devaney, John; Frederick, John; Betz, Gail (Journal of family violence, 2025)
Purpose Childhood exposure to intimate partner violence (IPV) is a pervasive problem worldwide. In addition to directly observing or indirectly experiencing IPV, children may be killed because of IPV. To date, research on child IPV-related deaths exists in various, disconnected areas of scholarship, making it difficult to understand how IPV contributes to child fatalities. As such, this scoping review located and synthesized research on child fatalities that resulted from IPV, seeking to understand the state of global research concerning the prevalence and circumstances of IPV-related child fatalities. Methods Using a combination of keywords and subject terms, we systematically searched PsycINFO, CINAHL Plus, PubMed, and seven research repositories. We located empirical studies published in English in peer-reviewed journals that reported findings concerning children (aged 0–17) who were killed because of IPV and/or people who killed children due to IPV. Among 9,502 de-duplicated records, we identified 60 articles that met review inclusion criteria. We extracted and synthesized information concerning research methods, circumstances and consequences of the fatalities, characteristics of people who committed IPV-related homicide of a child, and characteristics of children who died because of IPV. Results Studies were published from 1986–2022 and analyzed data from 23 countries. Most studies did not focus exclusively on IPV-related child homicides, and overall, studies reported sparse information concerning the contexts and circumstances of such fatalities. There were two predominant and distinct groups of children killed due to IPV: children killed by a parent or other adult caregiver and adolescents killed by an intimate partner. It was often difficult to ascertain whether the demographic characteristics of individuals who kill a child in the context of IPV and other contextual details might be similar to or different from child fatalities that occur under different circumstances or for other motivations. Conclusions This review highlighted that children die because of IPV. Findings indicated that such fatalities, while maybe difficult to predict, are often preventable if earlier intervention is made available and professionals are alert to key circumstances in which fatality risk is high. Future research and practice efforts should attend to understanding child fatalities resulting from IPV to identify critical intervention points and strategies that will save children’s lives.